2020
DOI: 10.1002/pds.4987
|View full text |Cite
|
Sign up to set email alerts
|

Medication burden and frailty in older adults with intellectual disability: An observational cross‐sectional study

Abstract: Purpose: Recently, efforts have been made to quantify frailty among older adults with intellectual disability (ID). Medication exposure is associated with frailty among older adults without ID. However, there is little research on this association among older adults with ID. The aim of this study was to examine specifically in people with ID the association between frailty and medication exposure, including anticholinergic and sedative medication exposure. Methods: Data were drawn from Wave 2 (2013/2014) of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 44 publications
3
21
0
Order By: Relevance
“…From the clinical treatment perspective, older patients with depressive symptoms often have concurrent with sleep disorders and increased medication burdens including sedative-hypnotic drugs and antidepressants [ 45 ]. Apart from polypharmacy, several studies have shown that taking sedative-hypnotic drugs is significantly associated with poor physical function, poor appetite and frailty [ 46 48 ]. Antidepressants, as one of the important pharmacological treatment options for clinically diagnosed depressive and anxiety disorders, are associated with frailty, which may increase the risk of adverse effects [ 49 ], falls [ 50 ], and fractures [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the clinical treatment perspective, older patients with depressive symptoms often have concurrent with sleep disorders and increased medication burdens including sedative-hypnotic drugs and antidepressants [ 45 ]. Apart from polypharmacy, several studies have shown that taking sedative-hypnotic drugs is significantly associated with poor physical function, poor appetite and frailty [ 46 48 ]. Antidepressants, as one of the important pharmacological treatment options for clinically diagnosed depressive and anxiety disorders, are associated with frailty, which may increase the risk of adverse effects [ 49 ], falls [ 50 ], and fractures [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…From the clinical treatment perspective, older patients with depressive symptoms often have concurrent with sleep disorders and increased medication burdens including sedativehypnotic drugs and antidepressants [45]. Apart from polypharmacy, several studies have shown that taking sedative-hypnotic drugs is significantly associated with poor physical function, poor appetite and frailty [46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…Medications with both anticholinergic and sedative effects were included in one group to avoid duplication. In the current study, we classi ed participants as having no exposure (DBI = 0), low exposure (0 < DBI < 1), or high exposure (DBI ≥ 1) [31].…”
Section: Medication Exposurementioning
confidence: 99%
“…Among several scales or indexes using a similar approach, the ACB scale has recently been reported to show prognostic utility in terms of mortality 31 . In the older adult population, a growing body of evidence has shown that ACB has a more substantial impact on adverse outcomes and the exacerbation of comorbidities than in younger adults 32–34 . We hypothesized that ACB would associate with inadequate nutrition in older age.…”
Section: Introductionmentioning
confidence: 99%
“…31 In the older adult population, a growing body of evidence has shown that ACB has a more substantial impact on adverse outcomes and the exacerbation of comorbidities than in younger adults. [32][33][34] We hypothesized that ACB would associate with inadequate nutrition in older age. Therefore, our aim in this study was to examine the potential association between ACB and nutrition status in community-dwelling older adults.…”
Section: Introductionmentioning
confidence: 99%